Ordered mesoporous titanium oxide for thin film microbatteries with enhanced lithium storage. (1st June 2015) - Ortiz, Gregorio F.; Berenguer-Murcia, Ángel; Cabello, Marta; Cazorla-Amorós, Diego; Tirado, José L.
Graphical abstract: Highlights: 3D ordered mesoporous binder-free TiO2 electrode exhibited improved Li storage. The hexagonal packing accounts for a better connectivity and lithium diffusivity. Maximum capacity of 470 μA h cm −2 μm −1 over 100 cycles is achieved. Abstract: A 3D mesoporous TiO2 material with well-developed mesostructure is prepared in the form of a binder-free thin (100 nm) film and studied as potential candidate for the negative electrode in lithium microbatteries. By appropriate thermal treatments, the selected crystal structure (anatase, rutile, or amorphous), and micro-/mesostructure of the materials was obtained. The effects of voltage window and prelithiation treatment improved first cycle reversibility up to 86% and capacity retention of 90% over 100 cycles. After a prolonged intercalation of lithium ions in ordered mesoporous TiO2 appeared small particles assigned to Li2 Ti2 O4 with cubic structure as observed from ex-situ TEM micrographs. This study highlights the flexibility of the potential window to which the electrode can operate. Maximum capacity values over 100 cycles of 470 μA h cm −2 μm −1 and 177 μA h cm −2 μm −1 are obtained for voltage ranges of 0.1–2.6 V and 1.0–2.6 V, respectively. The observed values are between 6 and 2 times higher than those obtained for films with 600 nm (80 μA h cm −2 μm −1 ) and 900 nm (92 μA h cm −2 μm −1 ) lengths. This indicates that 100 nm thin TiO2 films with high accessibility show finite-length type diffusion which is interesting for this particular application.